ISOLASI DAN IDENTIFIKASI SENYAWA GOLONGAN FLAVONOID PADA DAUN NANGKA (Artocarpus heterophyllus Lmk) DAN AKTIVITAS ANTIBAKTERI TERHADAP BAKTERI Staphylococcus aureus - Darmawati, Anak Agung Sagung Krisna; Bawa, I Gusti Agung Gede; Suirta, I Wayan (Jurnal Kimia (Journal of Chemistry); Vol. 9, No. 2 Juli 2015, 2015)
Isolation, identification and antibacterial activity of flavonoid compounds from jackfruit leaf (Artocarpus heterophyllus Lmk) extract have been done in this research. Extraction of 500 g dry powder of jackfruit leaf using maceration method produced 31.20 g concentrated brownish green ethanol extract. Partition of 30.00 g the ethanol extract gained three concentrated extracts in n -hexane (4.46 g), chloroform (0.84 g) and n -buthanol (6.65 g) fractions. The phytochemical test showed that n -buthanol extract contained flavonoid compound which was active as antibacterial agent with 15.75 mm inhibition capacity. Column chromatography analysis on n -buthanol extract with mobile phase n -hexana: ethyl acetate: n -butanol (8:2:1) gave 8 fractions (FA, FB, FC, FD, FE, FF, FG, FH).  Phytochemical testing showed that fraction FA and fraction FH belong to flavonoide compounds. Analysis of FA using UV-Visible gained 2 peaks at ? 323.40 nm (band I) and ? 285.60 nm (band II) which indicated the flavonoide groups of flavanone or dihydroflavonol. Analysis of FH using UV-Visible gained 2 peaks at ? 323.40 nm (band I) and ? 285.60 nm (band II) suggested the flavonoide groups of flavone or flavonol (3-OH substitution).` By using shiffting reagent the isolate FA was suggested to contain dihydroflavonol group and FH was suggested to contain flavone with hydroxyl groups at C-2’, C-4’.C-5’, C-6’, C-6, C-7, and C-8. Infrared analysis showed that the isolate had –OH, C=O, C-O, C=C aromatic, CH aromatic, and CH aliphatic groups. Antibacterial testing of flavonoid compounds of fraction A and fraction H on Staphylococcus aureus with a concentration of 10.000 ppm inhibited 10.50 mm for fraction A and 7.25 mm for fraction H.
Keywords: Dihidroflavonol, Flavone, Artocarpus heterophyllus Lmk., Antibacterial, Staphylococcus aureus